Development, characterization and solubility enhancement of comparative dissolution study of second generation of solid dispersions and microspheres for poorly water soluble drug - Poovi Ganesan; Rajpriyadarsini Soundararajan; Uma Shanmugam; Vinothini Ramu (Elsevier, 2015)
The poor dissolution characteristics of water-insoluble drugs are a major challenge for pharmaceutical scientists. Reduction of the particle size/increase in the surface area of the drug is a widely used and relatively simple method for increasing dissolution rates. The objective of this study was to improve solubility, release and comparability of dissolution of a poorly soluble drug using two different types of formulations (solid dispersions and microspheres). Hydrochlorothiazide was used as a model drug. The solid dispersions and microspheres were prepared by solvent evaporation method using ethyl cellulose, hydroxypropyl methylcellulose in different drug-to-carrier ratios (1:1, 1:2 w:w). The prepared formulations were evaluated for interaction study by Fourier transform infrared spectroscopy, differential scanning calorimetry, percentage of practical yield, drug loading, surface morphology by scanning electron microscopy, optical microscopy and in-vitro release studies. The results showed no interaction between the drug and polymer, amorphous state of solid dispersions and microspheres, percentage yield of 42.53% to 78.10%, drug content of 99.60 % to 99.64%, good spherical appearance in formulation VI and significant increase in the dissolution rate.